Positive 2D discrete-time linear Lyapunov systems - Przyborowski, Przemysław; Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
Two models of positive 2D discrete-time linear Lyapunov systems are introduced. For both the models necessary and sufficient conditions for positivity, asymptotic stability, reachability and observability are established. The discussion is illustrated with numerical examples.
Keywords: positivity; Lyapunov systems; reachability; observability